Variation of thermophysical properties of clay with adsorption optimization. (2010)
Clays have some properties which make them good adsorbents. The adsorption of heavy metal ions by clay usually affects its thermal properties and these properties have direct influence on seed germination and crop growth. In this study, the variation of thermophysical properties of clay with adsorption of some heavy metal ions at different concentrations was investigated. An Atomic Absorption Spectrophotometer (AAS) was used to determine the concentrations in the samples. A known mass of clay sample was mixed with certain volume of already prepared Pb (II), Cd (II), Cu (II), Ni (II), and Zn (II) solutions of different concentrations; after which some cylindrical pellets were made from the mixture of the clay sample with aqueous solutions of different concentrations and the thermal properties determined. The transient measurement technique was used in this work to determine the thermal properties of doped clay. Results showed that Copper had the highest ion exchange in the clay, while Cadmium had the lowest ion exchange. The thermal conductivity of clay increases with increase in the concentration of heavy metal being adsorbed by the clay to a considerable level. The lowest thermal conductivity was found to be 9.5824W/mK (preliminary study) and the highest was found to be 10.5010 W/mK. Thermal diffusivity ranged from 2.69674x 10-6m2/s to 3.47991x 10-6m2/s. However, For all the samples, thermophysical properties increases as the concentration increases to a certain optimum level above which cation exchange is no longer possible. From the results, it can be concluded that the concentration of heavy metals being adsorbed by clay affects its thermal properties. Increase in the rate of heat being conducted by clay usually leads to poor seed germination, poor crop growth, rotting, etc. in agricultural sector.